2017
DOI: 10.1159/000481394
|View full text |Cite
|
Sign up to set email alerts
|

Efferent Axonal Projections of the Habenular Complex in the Fire-Bellied Toad <b><i>Bombina orientalis</i></b>

Abstract: The habenular complex and its associated axonal pathways are often thought of as phylogenetically conserved features of the brain among vertebrates despite the fact that detailed studies of this brain region are limited to a few species. Here, the gross morphology and axonal projection pattern of the habenular complex of an anuran amphibian, the fire-bellied toad Bombina orientalis, was studied to allow comparison with the situation in other vertebrates. Axonal pathways were traced using biocytin applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 39 publications
1
8
2
Order By: Relevance
“…In contrast, in birds and mammals habenular asymmetry was not described as regards the distribution of these proteins (Braun, ; Celio, ; Résibois & Rogers, ). Moreover, in amphibians habenular asymmetry has been observed in urodeles, but not all species of anurans share this feature (Guglielmotti, Cristino, Sada, & Bentivoglio, ; Morona & González, ), although they might indeed possess asymmetry in their connectivity (Laberge & Smith, ). It is noteworthy that as in basal actinopterygian fishes (Graña et al, ; López, Perlado, Morona, Northcutt, & González, ; Lozano, Morona, & González, 2016), CB is found in cholinergic cells in the dorsal habenula of lungfishes (López et al, ) and both markers stain the fasciculus retroflexus, which marks the boundary between p2 and p1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in birds and mammals habenular asymmetry was not described as regards the distribution of these proteins (Braun, ; Celio, ; Résibois & Rogers, ). Moreover, in amphibians habenular asymmetry has been observed in urodeles, but not all species of anurans share this feature (Guglielmotti, Cristino, Sada, & Bentivoglio, ; Morona & González, ), although they might indeed possess asymmetry in their connectivity (Laberge & Smith, ). It is noteworthy that as in basal actinopterygian fishes (Graña et al, ; López, Perlado, Morona, Northcutt, & González, ; Lozano, Morona, & González, 2016), CB is found in cholinergic cells in the dorsal habenula of lungfishes (López et al, ) and both markers stain the fasciculus retroflexus, which marks the boundary between p2 and p1.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore argued that the context, in which the habenula circuitry is recruited might have changed (Stephenson‐Jones, Floros, et al, ). Habenular efferents terminate predominantly in diencephalic, mesencephalic, and rhombencephalic areas, with an additional forebrain projection in tetrapods [lampreys: Yáñez & Anadón, , Stephenson‐Jones, Floros, et al, ; chondrichthyes: Giuliani et al, ; teleosts: Villani et al, , Yáñez & Anadón, , Amo et al, ; amphibians: Kemali et al, , Laberge & Smith, , present study; reptiles: Distel & Ebbesson, , Díaz & Puelles, ; mammals: Cragg, , Akagi & Powell, , Smaha & Kaelber, , Herkenham & Nauta, , Araki, McGeer, & Kimura, ]. In the course of vertebrate evolution, the primordial habenula circuitry seemingly underwent various evolutionary adaptations and the complexity of the afferent and efferent connectivity increased in the tetrapod line.…”
Section: Discussionmentioning
confidence: 54%
“…In the following, arguments are provided which support a homology of the anuran DHb and VHb to mammalian MHb and LHb, respectively. This contradicts the assessment of Laberge and Smith (), who suggested that the conservation of the habenula circuitry among vertebrates is overestimated. Figure displays the habenula circuitry in key positions during evolution.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations